Tinospora cordifolia (Willd.) Miers: phytochemical composition, cytotoxicity, proximate analysis and their biological activities - Modi, Bindu; Koirala, Niranjan; Aryal, Surya Prasad; Shrestha, Jiban; Koirala, Shishir; Upadhyaya, Jitendra; Basnyat, Ram Chandra; Nassan, Mohamed A.; Alqarni, Mohammed; Batiha, Gaber El-Saber (Cellular and Molecular Biology, 2021)
The present research work has been performed to evaluate the phenolic content, flavonoids content, and cytotoxicity of a multidimensional medicinal plant; Tinospora cordifolia and as well as to determine nutritive value by proximate analysis. The total phenolic and flavonoids contents of Tinospora cordifolia were found to be significantly greater in methanol extract as compared to corresponding hexane extract. Brine shrimp bioassay indicated Tinospora cordifolia is pharmacologically active. The percentage composition of different nutrition parameters namely moisture, total ash, crude fat, protein, fibre, carbohydrate, and vitamin C were assessed. The nutritive values of fresh and dried stem samples were evaluated as 156.44 Kcal/100g and 232.61 Kcal/100g respectively. From Gas column mass spectrometry analysis, it can be reported that inositol, 1-deoxy-, trans-sinapyl alcohol, n-hexadecanoic acid were present in the major amount in methanol stem extract. The findings from this study reveal Tinospora cordifolia contains an adequate amount of phenolic and flavonoids content, vital bioactive antioxidant compounds, and a good source of carbohydrates and fibers which potentially adds to the overall value of the plant.